Poesia e profecia: a espiritualidade das Comunidades Eclesiais de Base e um aporte das canções de Zé Vicente - Tavares, Emerson Sbardelotti (2024)
The present work, entitled Poetry and Prophecy: The Spirituality of Base Ecclesial Communities and a contribution from the Songs of Zé Vicente, has as its primary objective to analyze the importance of Poetry and Prophecy, through the Spirituality experienced in Base Ecclesial Communities (CEBs), from of the contributions made by the lyrics of Zé Vicente's songs. The proposal is to revisit, following the documentary bibliographic method, Liberation Theology and Liberation Spirituality, following Jesus of Nazareth, based on the teachings and thoughts of Pope Francisco; and the bridge built by Poetry and Prophecy contained in Zé Vicente's songs that animate and sustain the mission and commitment of the Base Ecclesial Communities as a locus theologicus in the defense of Life in a context of intolerance, discrimination and hatred that has sickened and weakened humanity. Given this reality, the research has as its Central Question: Why research the relationship between poetry, prophecy, spirituality of the Base Ecclesiastical Communities and a contribution from Zé Vicente's songs? Faced with this reality, this research aims to design a path that is a bridge, that connects, that reconnects Liberation Theology with Poetry, Liberation Spirituality with Prophecy, Prophecy and Poetry with Base Ecclesial Communities, bringing people closer to the Option for the Poor germinated and spread in songs by Zé Vicente. The development of this research was organized into two parts: the first, dedicated to the presentation, re-presentation and encouragement of Liberating Art and Liberation Theology as a playful and theological approach to the urgent issues of the current moment. The second part discusses the fundamental issues of Poetry, Prophecy and Spirituality experienced in Base Ecclesiastical Communities, based on the Songs of the Walk. As a result of the research, it is understood that Liberation Theology, Liberation Spirituality, Base Ecclesiastical Communities are themes of great importance, necessity and urgency for the understanding and experience of prophecy and synodality: the praxis of a Church on the way out. Final considerations point to the need to know and delve deeper into the work of Zé Vicente, where his poetry feeds on the diversity of causes, rhythms, colors, smells and genders of our people